(untitled) (Physical Education, Health and Social Sciences, 2025)
This study examines the representation of traditional and Western clothing in Pakistani cinema through screen time-based content analysis of two high-budget films: Jawani Phir Nahi Aani 2 (2018) and Money Back Guarantee (2023). Clothes in movies are a powerful visual tool that shape perception of culture, identity, and modernity. Pakistani films have dominant by Western culture, while traditional and national outfits such as the Shalwar Kameez receive limited screen visibility. Using quantitative content analysis researchers calculated the duration (time per frame) of different dress such as jeans, flowy maxi dresses, lehengas, suits, and traditional costume to point out trends in wardrobe representation. Findings revealed dominancy of Western and modern garments in the selected movies. In the film titled “Jawani Phir Nahi Aani 2,” the lead heroine appears in shalwar kameez for only 4.63% of total screen time, while in tight jeans and Western tops for 28.78%, flowy maxi dresses for 13.99%, and lehengas with visible midriffs for 29.68%. In movie named “Money Back Guarantee” the lead heroine portrayed in tight jeans for 44.67% of the screen time, while the lead actor is framed purely in Western suits. These findings indicate a significant shift towards Western aesthetics in Pakistani cinema, reflecting broader cultural shifts and growing cinematic preferences. Based on the findings it is attractive for new generation but on the other side it will also raises question about the marginalization of cultural clothing, traditional values and norms.